PEDAGOGY AS A COOLABORA INSTRUMENT IN THE BUILDING OF AN ADEQUATE SOCIAL ETHICS. (Fiep Bulletin - online, 2015)
The objective of this work is to find a bigger direction in pedagogical making that we undertake, better understanding in the walking towards an after-modern world in For such reason, we delved into the concept of Ethics in Aristotle, therefore, we believe that its belief meets ours, or either, for the philosopher, the Ethical one was synonymous of "Fair good life ". To reach the accomplishment of this concept, it still is, and perhaps will always be the biggest challenge of the humanity. The intersession between the Ethics and the Education, just to mention, never was so current, when the country  is passing through one of its worts crises. We see that the Pedagogy has a very important role in this guiding, for being historically an art and a science, with the objectives to take the man towards education, the instruction and also his/her formation. In this way our hypothesis is  that the school becomes together a co-responsible collaborator with the family in the educative process of the human being. Subjects as ethical as others directly related to the context of the apprentice, must be an axle to interdisciplinary of the school's grades and that you discipline them. Having different visions in the formation of the school's grades, generates new strategies in the organization of the work concerned with the development of the thinking and the formation of the apprentice. They are methodologies that make a hard  contextualized situation, having the apprentice as the builder of its concepts, procedures and attitudes. Briefly, the presented methodology considers a work directed towards the school humanization, collective of historical citizens as a part of the native construction of a citizen's ethics. "The native land does not exist without freedom, nor the freedom without the virtue, nor the virtue without the citizens" (ROSSEAU)
Keywords: ethics education methodology